: A case report of re-challenge of immune checkpoint inhibitors after immune-related neurological adverse events: Review of literature. Issue 36 (9th September 2022) - Moon, Heesung; Kim, Seul-Gi; Kim, Seung Ki; Kim, Jinkwon; Lee, Seung Ryeol; Moon, Yong Wha
Abstract : Introduction: The indications for immune checkpoint inhibitors (ICIs) are expanding for various cancers because of their durable responses and tolerable safety profiles. Immune-related adverse events (irAEs), including neurological adverse events (nAEs), are associated with ICIs therapy. However, there have been few studies on whether re-challenge with ICIs can be clinically acceptable after neurological AE has improved. Patient concerns: A 69-year-old woman with recurrent ovarian cancer undergoing palliative chemotherapy was admitted to our hospital with sudden development of diplopia, dizziness, and gait instability. The patient was administered ICI therapy with anti-angiogenic agents for 9 weeks for 3 cycles. Diagnosis: We performed neurological examination, brain imaging, nerve conduction studies, and serology tests. The patient was diagnosed with Guillain–Barré syndrome variant, an immune-mediated polyneuropathy characterized by a triad of ataxia, areflexia, and ophthalmoplegia. Intervention: After prompt discontinuation of pembrolizumab, the patient was taken intravenous methylprednisolone (2 mg/kg) was administered for 5 days, and her symptoms were partially resolved. With the addition of immunoglobulin 0.4 g/kg for 5 days, her symptoms gradually improved. Outcomes: The patient's neurological symptoms improved after immunosuppressive therapy, without sequelae. The NCV showed normal nerve conduction. Unfortunately, because there was little evidence for pembrolizumab rechallenge, pembrolizumab therapy was permanently discontinued, and the tumors eventually progressed.